IFN-Alpha receptor-1 upregulation in PBMC from HCV naïve patients carrying cc genotype. possible role of IFN-lambda. - Eleonora Lalle; Licia Bordi; Claudia Caglioti; Anna Rosa Garbuglia; Concetta Castilletti; Chiara Taibi; Francesca Cristofari; Maria Rosaria Capobianchi (PLoS ONE)
Background and aims IL-28B gene polymorphisms predict better therapeutic response and spontaneous clearance of HCV. Moreover, higher expression of IFN-lambda has been reported in patients with the rs12979860 CC favourable genotype. The study aim was to establish possible relationships between IL-28B rs12979860 genotypes and expression of IFN-alpha receptor-1 (IFNAR-1) in naïve HCV patients, and to explore the possible role of IFN-lambda. Methods IFNAR-1 mRNA levels were measured in PBMC from naïve patients with chronic hepatitis C with different IL-28 genotypes. The ability of IFN-lambda to up-regulate the expression of IFNAR-1 was established in PBMC from healthy donors carrying different IL-28B genotypes. Results Lower IFNAR-1 mRNA levels were observed in PBMC from HCV-infected naïve patients as compared to healthy donors. In healthy donors, IFNAR-1 mRNA levels were independent from IL-28B genotype, while in HCV patients, an increasing gradient was observed in TT vs CT vs CC carriers. In the latter group, a direct correlation between IFNAR-1 and endogenous IL-28B expression was observed. Moreover, IFN-lambda up-regulated IFNAR-1 expression in normal PBMC in a time-and dose-dependent manner, with a more effective response in CC vs TT carriers. Conclusion Endogenous levels of IFN-lambda may be responsible for partial restoration of IFNAR-1 expression in HCV patients with favourable IL-28 genotype. This, in turn, may confer to CC carriers a response advantage to either endogenous or exogenous IFN-alpha, representing the biological basis for the observed association between CC genotype and favourable outcome of either natural infection (clearance vs chronicization) or IFN therapy.